Seasonality of gestational diabetes mellitus and maternal blood glucose levels: Evidence from Taiwan. Issue 41 (9th October 2020) - Wang, Panchalli; Wu, Chung-Shing; Li, Chung-Yi; Yang, Chun-Pai; Lu, Mei-Chun
Abstract : Abstract: Previous studies have indicated that the prevalence of gestational diabetes mellitus (GDM) was related to the season. However, there was no relevant information in Asia. The aim of this study was to determine whether there was seasonality of GDM and maternal blood glucose level in Taiwanese women. A total of 6396 pregnancies were enrolled between 2012 and 2014 in this retrospective study. A 2-step approach according to the Carpenter-Coustan criteria was used for GDM diagnosis. A generalized linear mixed model was used to estimate the effect of season on GDM diagnosis by adjusting for age, prepregnancy body mass index, parity, history of GDM, fetal sex, and the rate of weight gain. During the study period, 418 (6.5%) pregnancies were diagnosed as GDM. The model demonstrated an increased prevalence of GDM in spring and summer (odds ratio: 1.59, 95% confidence interval: 1.13–2.24; odds ratio: 1.59, 95% confidence interval: 1.14–2.23, respectively) compared to winter. For the glucose level variation, the model demonstrated an increase of 2.56 mg/dL glucose in the 50-g glucose challenge test in summer compared to winter. In glucose challenge test-positive pregnancies, the season also had an effect on the results of the 100-g 1-h, 2-h, and 3-h oral glucose tolerance tests, but no effect on the 100-g fasting oral glucose tolerance tests. GDM prevalence in Taiwan presents seasonal variation, with the highest risk during spring and summer due to post-glucose load level variations. These findings could serve as reference data for countries in Southeast Asia or areas with a similar climate.